A Comparative Study of the Arguments of Hadith Scholars and Theologians in the Interpretation of Divine Attributes - Muhammad Usama; Professor Dr. Altaf Hussain Langrial (Journal of Religion and Society, 2025)
This research article explores the interpretations of the Qur'anic Āyāt al-Ṣifāt (verses of Divine Attributes) in the light of classical and post-classical Islamic theology (ʿIlm al-Kalām). It focuses on the diverse theological approaches of prominent Muslim theologians (Mutakallimūn) such as the Ashʿarīs, Māturīdīs, and Ḥanbalīs regarding the affirmation, allegorical interpretation (taʾwīl), or delegation (tafwīḍ) of these attributes. The study aims to highlight the epistemological and methodological principles adopted by each school, their theological implications, and the impact of their views on later Islamic thought. By critically examining their arguments and contextualizing them within broader kalām debates, this paper contributes to a deeper understanding of how Muslim theologians grappled with the balance between divine transcendence and textual fidelity. Keywords: Arguments, Hadith Scholars, Theologians, Interpretation of Divine Attributes